Reducing building greenhouse gas emissions through climate plan adoption - Salvatorelli, Anna (Kansas State University, 2019)
In 2017, the U.S. withdrew from the Paris Agreement, an international agreement with a goal to lower greenhouse gas emissions and keep global temperature rise of the current century below 2 degrees Celsius above pre-industrial levels. Stated reasons for the withdrawal was the burdening of American citizens with tax costs, lost jobs, lower wages, industry shutdowns, and diminished economic production. As a reaction, 407 U.S. city mayors signed a statement agreeing to uphold the Agreement’s climate goals. Many of these cities have reaffirmed existing climate plans or are creating new climate plans to combat climate change from the expected rise of greenhouse gas levels. A climate plan is a document that guides a city through actions towards reduced greenhouse gas emissions. The plans organize strategies, actions, and resources needed to reach specified climate goals. As commercial buildings can contribute a large percent of energy use and emissions of a city, a climate plan should focus a section of their plan on commercial buildings. The goal of this report is to inform cities on the adoption process of a climate plan through design, development, implementation, enforcement, and reporting as well as present common building strategies. Nine existing city climate plans are summarized with progress towards climate goals presented. The cities are analyzed based on emission reduction progress, plan content, implementation, and specific building strategies. This analysis is intended to provide direction for cities investigating the feasibility of adopting a climate plan.
Keywords: Climate plan; Emissions; Commercial buildings